Transformational Leadership in Changing the Education Paradigm: Improving the Quality of Alpha Generation Student - Karomi, Ahmad Danial; Mamlukhah, Mamlukhah (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to interpret transformational leadership in changing the educational paradigm, namely in improving the quality of learning of alpha generation madrasah aliyah students. The research design used is qualitative research with a case study method. The sources of informants in this study consisted of principals, teachers, students, and student guardians. Data collection in this study was conducted through three main methods, namely in-depth interviews, participatory observation, and document analysis. The results of this study show that transformational leadership at MAN 2 Banyuwangi has succeeded in changing the educational paradigm, namely in improving the quality of learning through soft skills development, digital learning hub development, and multimodal literacy development. The novelty in this research is the concept of transformational leadership that contributes to the quality of learning. The contribution of this study shows that the application of transformational leadership in Madrasah Aliyah can significantly change the educational paradigm.